2009
DOI: 10.1093/aje/kwp135
|View full text |Cite
|
Sign up to set email alerts
|

Ideal Weight and Weight Satisfaction: Association With Health Practices

Abstract: Evidence suggests that individuals have become more tolerant of higher body weights over time. To investigate this issue further, the authors examined cross-sectional associations among ideal weight, examination year, and obesity as well as the association of ideal weight and body weight satisfaction with health practices among 15,221 men and 4,126 women in the United States. Participants in 1987 reported higher ideal weights than participants in 2001, an effect particularly pronounced from 1987 to 2001 for yo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
73
0
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(86 citation statements)
references
References 28 publications
9
73
0
4
Order By: Relevance
“…Given that boys are self-reporting relatively high levels of dietary restraint ) and dieting appears to be directly influenced by social pressures, intervention programs that target messages about weight, dieting, and physical appearance may reduce boys' risk for developing dietary restraint. Based on Stice, Shaw, and Marti's (2007) meta-analytic review of eating disorder prevention programs for female adolescents, school-based prevention programs that are interventionist led and multisession could simultaneously target biological (e.g., cardiorespiratory fitness), psychological (e.g., body satisfaction and self-esteem), and social (e.g., social pressures) factors to reduce the potential for In addition, cardiorespiratory fitness played an important role in boys' body satisfaction, self-esteem, and self-reported dietary restraint in the present study, which is consistent with longitudinal research that found that cardiorespiratory fitness led directly to lower levels of selfreported dietary restraint and BMI in men over a 14 year time span (e.g., Kuk et al, 2009). …”
Section: Limitations Implications and Directions For Future Researchsupporting
confidence: 89%
See 2 more Smart Citations
“…Given that boys are self-reporting relatively high levels of dietary restraint ) and dieting appears to be directly influenced by social pressures, intervention programs that target messages about weight, dieting, and physical appearance may reduce boys' risk for developing dietary restraint. Based on Stice, Shaw, and Marti's (2007) meta-analytic review of eating disorder prevention programs for female adolescents, school-based prevention programs that are interventionist led and multisession could simultaneously target biological (e.g., cardiorespiratory fitness), psychological (e.g., body satisfaction and self-esteem), and social (e.g., social pressures) factors to reduce the potential for In addition, cardiorespiratory fitness played an important role in boys' body satisfaction, self-esteem, and self-reported dietary restraint in the present study, which is consistent with longitudinal research that found that cardiorespiratory fitness led directly to lower levels of selfreported dietary restraint and BMI in men over a 14 year time span (e.g., Kuk et al, 2009). …”
Section: Limitations Implications and Directions For Future Researchsupporting
confidence: 89%
“…In a longitudinal study of men, Reboussin et al (2000) found that CRF (as assessed by a graded exercise treadmill test to exhaustion) predicted lower levels of appearance dissatisfaction over the proceeding four weeks. Kuk et al (2009) found that men's CRF (as assessed by an objective measure of VO2max) was related positively to weight satisfaction and inversely correlated with mens' weight discrepancy (i.e., the difference between self-reported ideal and actual weight) 14 years later. Overall, middle school boys who are fit would likely feel instrumental in terms of their physical abilities and what their bodies can do (Lindwall, 2002;Marsh & Redmayne, 1994;Ricciardelli, McCabe, & Ridge, 2006).…”
Section: Cardiorespiratory Fitness and Body Dissatisfactionmentioning
confidence: 94%
See 1 more Smart Citation
“…Given that boys are self-reporting relatively high levels of dietary restraint ) and dieting appears to be directly influenced by social In addition, cardiorespiratory fitness played an important role in boys' body satisfaction, self-esteem, and self-reported dietary restraint in the present study, which is consistent with longitudinal research that found that cardiorespiratory fitness led directly to lower levels of selfreported dietary restraint and BMI in men over a 14 year time span (e.g., Kuk et al, 2009). …”
Section: Limitations Implications and Directions For Future Researchsupporting
confidence: 89%
“…Entre indivíduos na faixa etária dos 19 aos 35 anos, que praticavam algum tipo de atividade física, quer fossem atletas ou não-atletas, foi observado maior autoestima e melhor aceitação corporal que entre os considerados sedentários 31 . À medida que o aumenta o IMC, também a insatisfação com o corpo foi elevada, o que se reflete sobre a prática de atividade físi-ca, pois os indivíduos mais satisfeitos com sua aparência corporal tendem a praticar mais atividades físicas, principalmente os do sexo masculino 32 .…”
Section: Discussionunclassified